A phase IIb, randomised, double-blind, placebo-controlled, dose-ranging investigation of the safety and efficacy of NTCELL® [immunoprotected (alginate-encapsulated) porcine choroid plexus cells for xenotransplantation] in patients with Parkinson's disease. (April 2019) - Snow, Barry; Mulroy, Eoin; Bok, Arnold; Simpson, Mark; Smith, Andrew; Taylor, Kenneth; Lockhart, Michelle; Lam, BB Janice; Frampton, Christopher; Schweder, Patrick; Chen, Benson; Finucane, Gregory; et al.
Abstract: Introduction: Regenerative therapies in Parkinson's disease aim to slow neurodegeneration and re-establish damaged neuronal circuitry. Neurotrophins are potent endogenous regulators of neuronal survival, development and regeneration. They represent an attractive regenerative treatment option in Parkinson's disease. Porcine choroid plexus produces a number of neurotrophins, and can be safely delivered to the striatum in an encapsulated formulation (termed NTCELL®) to protect them from immune attack. NTCELL® has shown regenerative potential in animal models of stroke, Huntington's disease and Parkinson's disease. Following promising results from an initial open label safety study of intra-striatal delivery of NTCELL® in human subjects, we sought to specifically investigate the safety and efficacy of NTCELL® for the treatment of Parkinson's disease. Methods: 18 patients aged 56–65 years with idiopathic Parkinson's disease of at least 5 years duration were randomised to receive either sham surgery (general anaesthesia and partial thickness burr holes) or intra-striatal delivery of NTCELL® (the 3 groups in the treatment arm receiving incremental NTCELL® doses). Results: At 26 weeks, we found no significant difference in total UPDRS scores ('on' and 'off'), UPDRS motor scores ('on' and 'off'), PDQ-39, UDysRS, timed walk or modified Hoehn and Yahr stage between patients implanted with NTCELL® and patients undergoing sham procedure. There were no serious adverse events or xenogeneic viral transmission during the study. Conclusion: The study did not meet its primary efficacy end-point of a change in UPDRS at 26 weeks post-intervention compared with baseline. Stereotactic NTCELL® implantation was safe and well tolerated. Highlights: Encapsulated choroid plexus cells (NTCELL®) produce a variety of neurotrophins. Intra-striatal NTCELL® implantation is safe and well tolerated. We found no change in outcome measures at 26 weeks following NTCELL® implantation.